Developing and evaluating a Portuguese-language meditation App for medical students: motivation, adherence, and emotional effects - Soares, Ana Rita; Soares, Sandra; Brandão, Tânia; Teixeira, Ricardo João; Tavares, Isaura (Frontiers in Psychology, 2025)
The well-being of medical students is affected by high stress levels. The relevance of a mindfulness mediation app (Med@Med) specifically produced to help medical students at a Portuguese medical school cope with stress was evaluated. The app, consisting of 21 short meditations, was totally developed in Portuguese to fulfill with the needs of some of the students. The motivations to use the app, adherence to it, and its emotional benefits were evaluated. A total of 147 medical students were enrolled in the study. Students completed questionnaires related to emotional regulation (Emotion Regulation of Others and Self) and emotional thermometers before the first meditation and at the end of the project. Before and after each meditation, the students were invited to identify their basic emotion (joy, fear, disgust, anger, or sadness), no perceived emotion, or no reply. Participants received daily motivational messages (scientific or in lay language) or no message during the first 7 days of the project and the retention was registered. The main motivations to use the Med@Med app were to experience meditation (33%), decrease stress/anxiety (25%), or implement a daily meditation routine (16%). The remaining motivations of the students were sleep improvement or enhancement of academic performance. The self-motivation to use the app was high (7.3 ± 3.2 on a 1–10 scale). Participants that received daily messages in lay language, which summarized scientific findings about the benefits of meditation, were more likely to continue to use the app. The emotions changed from pre- to post-practice, with an increase in self-identification with joy and decrease of fear and sadness. An improvement in the intrinsic emotional regulation subscale (p < 0.01) was detected. In comparison with age-matched students that did not use the Med@Med app, the students that used the app presented less emotional distress and anxiety as evaluated by emotional thermometers. This study shows that medical students are motivated to use a meditation app. The improvement of emotion-related parameters after the use of the Med@Med app is a promising result. The benefits of using the Med@Med meditation app prepared in Portuguese keeping in mind the needs of medical students should be evaluated in other Portuguese-speaking medical schools.